Analysis of Digital Image Rejection (RFA) inDiagnosticRadiology Services after the Application of Computed Radiography (CR) to the Hospitals in Area Semarang City - Gatot Murti Wibowo; Dwi Rochmayanti; M. Irwan Katili (Poltekkes Kemenkes Semarang, 2013)
The purpose of this study was to determine the rejection of digital image analysis procedure CR softcopy hereinafter referred to as RFA, and describe the profile and characteristics of the proportion image rejection (rejection rates) based on the operational conditions of CR.Quantitative research was conducted with the observational approach. Data were collected by random sampling from 1181 digital image system CR-1137 type 1 at A hospital and the total number of CR type 2 digital image at B hospital on the status of post-image processing. Profiles and characteristics of the CR-system rejection rate was 9.15% while the type 1 for type 2 CR-system is 4.57%. Largest percentage of CR image rejection on both failitas dominated by chest radiographic anatomy of the organ which is 69.44% (A) and 48.08% (B). The findings reject rates of 15.87% due to poor performance of x-ray equipment and distribution teridenfitikasinya reject rates based on radiographer in A hospital deserves special attention. Though the radiographer and the employment rate figures reject individually in “ A” hospital not correlated (0.67 more than p-value).